The Effectiveness of the RADEC Learning Model in Improving Student Learning Achievement - Ulum, Achmad Miftachul; Alfani, Moch. Farich; Zakaria, Abd Razak (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
Learning is closely related to student academic achievement as one of the indicators of success. In the era of Society 5.0, many learning models have not met effectiveness standards, thus requiring more relevant innovations. The RADEC (Read, Answer, Discuss, Explain, Create) model is an alternative that encourages active student involvement and enhances learning outcomes. This study aims to examine the effectiveness of the RADEC model in improving the academic achievement of elementary school students. The research employs a quantitative approach with a pretest-posttest control group experimental design involving two elementary school students. Data were collected through tests and observations and analyzed descriptively and inferentially using the Wilcoxon test to measure the effectiveness of the RADEC model in improving learning outcomes. The results indicate that the RADEC learning model effectively improves elementary students’ academic achievement through five active stages that promote critical thinking, creativity, and collaboration. The average posttest score of the experimental group reached 83.06. This model also strengthens intrinsic motivation, reflectivity, and 21st-century skills. The role of the teacher as a facilitator and ongoing training are key to the successful and meaningful holistic implementation of the model. This study contributes to the development of innovative learning models relevant to the needs of 21st-century education. The RADEC model proves capable of enhancing student academic achievement, critical thinking skills, creativity, and collaboration. The findings serve as a reference for educators and policymakers in designing effective learning strategies and encourage continuous teacher training to improve the quality of education in elementary schools.